Bridges over troubled waters: South Asian women's movement confronting globalization - Menon-Sen, Kalyani (2002)
Kalyani Menon-Sen discusses how women's movements in South Asia are faced with the task of forging coalitions across national boundaries to challenge and resist macro-economic processes that are threatening their livelihoods and ways of life. A recent workshop highlighted the need for solidarity-building efforts to address areas of divergence and difference, many of which stem from the struggles of South Asian women to define their feminist visions within their own local contexts. - Reproduced.
Keywords: Womens liberation movement